RECURRENCE OF CHCV AFTER THE USE OF DIRECT ANTIVIRAL DRUGS: CLINICS, DIAGNOSIS, TREATMENT AND OUTCOMES (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Viral hepatitis C is one of the leading liver diseases. According to WHO, 70 million people are infected with this disease. HCV kills 290,000 people every year. In 95% of patients, the disease becomes chronic, and the main complications are fibrosis and cirrhosis of the liver. In some cases, a relapse is observed, despite treatment with antiviral drugs.